Exploração da força de trabalho indígena na formação dos seringais em Rondônia - Trubiliano, Carlos Alexandre Barros [UNESP] (Universidade Estadual de Maringa, 2017)
Between the late nineteenth century and the first decades of the twentieth century witnessed the economic cycles of the rubber in the Amazon region, promoting deep socio-spatial impacts. This article presents an overview of the exploitation of indigenous labor in the formation of rubber plantations in Rondônia. We will discuss worker's coping strategies, working conditions, and inter-ethnic contact. We aim at contributing to the debate on the expansion of capitalist relations in the Amazon region and the impacts of this process to the Rondônia indigenous populations.
Exploration of the indigenous workforce in the formation of syringes in Rondônia
Keywords: Capitalism; Indigenous; Seringals